2012
DOI: 10.1161/atvbaha.112.249391
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Toll-Like Receptors 7 and 9 Reduces Postinterventional Remodeling via Reduced Macrophage Activation, Foam Cell Formation, and Migration

Abstract: e72P ostinterventional remodeling is a critical determinant of long-term efficacy of percutaneous coronary interventions. Restenosis is characterized by acute elastic recoil and intimal hyperplasia attributable to inflammation, smooth muscle cell (SMC) proliferation, and extracellular matrix turnover. 1 Under hypercholesterolemic conditions, this is accompanied by influx and accumulation of low-density lipoprotein (LDL) cholesterol in the vessel wall that becomes oxidized and taken up by macrophages. Thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 47 publications
3
25
0
Order By: Relevance
“…Also, various diseases might differ in the overall complex response to TLR signaling. For example, postinterventional vascular remodeling is reduced by the combined blockade of TLR7 and TLR9, 31 whereas genetic deficiency of TLR7, as reported by Salagianni et al, 10 and TLR9, as reported here, causes acceleration of atherosclerosis. Notably, our data are consistent with recent findings indicating an emerging paradigm that endosomally located TLRs (eg, TLR3, TLR7) exert atheroprotection, whereas cell surface-located TLRs (eg, TLR2, TLR4) exert proatherosclerotic effects.…”
Section: Discussionsupporting
confidence: 63%
“…Also, various diseases might differ in the overall complex response to TLR signaling. For example, postinterventional vascular remodeling is reduced by the combined blockade of TLR7 and TLR9, 31 whereas genetic deficiency of TLR7, as reported by Salagianni et al, 10 and TLR9, as reported here, causes acceleration of atherosclerosis. Notably, our data are consistent with recent findings indicating an emerging paradigm that endosomally located TLRs (eg, TLR3, TLR7) exert atheroprotection, whereas cell surface-located TLRs (eg, TLR2, TLR4) exert proatherosclerotic effects.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, TLR3 plays a critical role in mediating atherosclerotic plaque instability, in part by modulation of macrophage matrix metalloproteinases-2 and -9 activities (Ishibashi et al, 2013). The contribution of endosomal TLR7 is beginning to emerge as a mediator of vascular remodeling and foam cell accumulation (Karper et al, 2012). Finally, endosomal TLR9 has been observed to propagate inflammation in response to vascular injury (Erridge et al, 2008;Lopez et al, 2012;Hirata et al, 2013), foam cell accumulation, and lesion formation (Niessner et al, 2006;Kim et al, 2009a;Sorrentino et al, 2010;Karper et al, 2012) and in LDL receptor-deficient mice (Ding et al, 2013).…”
Section: A Atherosclerosismentioning
confidence: 99%
“…84,85 Moreover, mitochondrial DNA in conjunction with antimicrobial peptide leads to activation of TLR9-mediated inflammation and atherosclerotic lesion formation in Apoe −/− mice. 86 Given the conflicting data on the role of both TLR7 and TLR9, for example, in vascular inflammation, [87][88][89][90] it currently remains unclear whether effects of eRNA (and extracellular DNA) on atherosclerosis and myocardial infarction are in part mediated by triggering immune responses targeted against self-nucleic acids that require signaling via particular TLRs. It is conceivable that eRNA exerts cell type-specific mechanisms and that the multiple cardiovascular functions of selfeRNA are mainly transmitted independently of TLR signaling.…”
Section: 81mentioning
confidence: 99%